Characterization of emitted light from travelling Gunn domains in Al0.08Ga0.92As alloy based Gunn devices. (November 2017) - Cetinkaya, Caglar; Mutlu, Selman; Donmez, Omer; Erol, Ayse
Abstract: We report room temperature operation of light emitters based on Al0.08 Ga0.92 As Gunn devices fabricated in a simple bar geometry with wedged-shaped electrodes. High-speed I-V measurements reveal that, at the threshold of negative differential resistance region at around 3.8 kV/cm, current instabilities, i.e., Gunn oscillations, are created with a 3.8 ns period. Both edge and surface light emission are observed when the device is biased at an electric field of onset of the negative differential resistance (NDR) region at around 3.8 kV/cm and the intensity of the light exponentially increases at applied fields just above NDR threshold likewise in a conventional laser. The origin of the light emission, which has peak wavelength is around 816 nm corresponds to the band-gap energy of Al0.08 Ga0.92 As, is recombination of electrons and holes generated by impact ionisation process in travelling space charge domains, i.e., Gunn domains. We demonstrate that, with increasing applied field, the amplitude of Gunn domains increases which is a result of the enhanced generation of electrons and holes via impact ionisation. The intensity of the emitted light is observed to be dependent on applied electric field. At low electric fields, light intensity increases linearly then, when applied electric field reaches the onset of NDR region, increases exponentially. Besides, as applied field is increased, full width at half maximum (FWHM) of emitted light decreases to 56.5 nm from 62 nm, evolving into higher selective emission line in wavelength. The light emission from the device is determined to be independent of the polarity of the applied voltage. A comparison of surface emission and edge emission characteristics of the waveguided device are different from each other. Edge emission has higher electroluminescence intensity and better spectral purity than surface emission with well-defined longitudinal modes of Fabry-Pérot cavity, which indicates that, in such a device, lasing action arises from the recombination of excess carriers generated via impact ionisation in travelling Gunn domains. Besides, the edge emission peak of waveguided Al0.08 Ga0.92 As Gunn device at 4.1 kV/cm is split into two peaks with FWHM of 8 and 6 nm as well as neighbouring sharper minor peaks due to stimulated emission dominates by building-up photons in the cavity. Our results reveal that the proposed Gunn device can be a promising alternative to conventional diode lasers with its simpler design, only one type doped active region and voltage polarity-independent operation, but the duty cycle has to be chosen small enough to make the device operate at room temperature. Highlights: Gunn oscillations are observed on the onset of the NDR at an n-type doped AlGaAs alloy. The devices based on n-type AlGaAs alloy starts surface and edge emitting at the onset of NDR at room temperature. The intensity of emitted light exponentially increases above NDR threshold. The devices operate at both voltage polarity. Emission spectrum exhibits sharp peaks for waveguided device above NDR threshold.